(untitled) (Indian Journal of Animal Production and Management, 2024)
The present exploratory study was carried out in four districts (Kangra, Hamirpur, Bilaspur and Una) of Himachal Pradesh, to study the ethnoveterinary practices used by Gaddi pastoralists during their low hill migration. Thirty flocks were randomly selected from the database of AICRP on Goat Improvement and field visits were made during October 2020- March 2021. Detailed proforma was designed to collect the information of ethnoveterinary prctices followed by Gaddi nomads. The survey study revealed that Gaddi nomads are till date using their traditional knowledge for treating different ailments of Sheep and Goat in migratory conditions. Ethnoveterinary practices are more significant to the Gaddi nomads as they are continuously migrating with their livestock throughout the year, without having prompt access to medical facilities provided by the state Animal Husbandry department along the migratory routes. Gaddi nomads use the ethnoveterinary practices for the treatment of various ailments viz. maggot wound, skin infection, diarrhea, indigestion, lantana poisoning, lameness, mastitis, tympany, retention of placenta (ROP), foot and mouth disease (FMD), respiratory problems, abortion, leech infestation, fracture, ticks & lice infestation and wounds.